2019
DOI: 10.1177/1687814019853964
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of demolition robot arm based on finite element method

Abstract: As a novel robot which mainly engages in the demolition and transformation of various concrete buildings, the demolition robot has developed rapidly in recent years. The impact force is mainly produced by the breaking hammer installed in the front end of the arm. As the most important part of a demolition robot, the boom arm is mainly composed of four parts including a supporting arm, a main arm, a fore arm, and a breaking hammer system. In this article, a mechanical model of the boom arm is established, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Crack formation as a result of the use of the hydraulic hammer was reported by Li et al (2019) [15] using Ansys Workbench which showed the behavior in the arm structure in an articulate system, when a hydraulic hammer is used. Fundamental parameters about the potential impact and crack formation were taken referentially from the registered real operations.…”
Section: Real Work Conditionsmentioning
confidence: 93%
“…Crack formation as a result of the use of the hydraulic hammer was reported by Li et al (2019) [15] using Ansys Workbench which showed the behavior in the arm structure in an articulate system, when a hydraulic hammer is used. Fundamental parameters about the potential impact and crack formation were taken referentially from the registered real operations.…”
Section: Real Work Conditionsmentioning
confidence: 93%
“…As one of the greatest inventions of mankind in the 20th century, great advances have been made in robotics since its inception in the early 1960s. Robots show great advantages over human beings for some jobs, particularly those that are tedious and repetitive, require high quality, or can cause harm to the human body. For example, service robots can help with health care, cleaning, and security; underwater robots can salvage shipwrecks and lay cables; and engineering robots can go up mountains and into caves. , Biointelligent robots, nanoscale robots in particular, have recently attracted attention for disease treatment, and they have been developed as next-generation drug transporting devices that are sensitive to molecular stimuli. A DNA nanorobot can be integrated into the drug delivery equipment for cancer therapeutics, driven by molecular triggers in vivo . , However, intelligent bionanorobots for in vivo heavy metal detoxification have almost not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1−4 For example, service robots can help with health care, cleaning, and security; 5 underwater robots can salvage shipwrecks and lay cables; 6 and engineering robots can go up mountains and into caves. 7,8 Biointelligent robots, nanoscale robots in particular, have recently attracted attention for disease treatment, and they have been developed as nextgeneration drug transporting devices that are sensitive to molecular stimuli. 9−18 A DNA nanorobot can be integrated into the drug delivery equipment for cancer therapeutics, driven by molecular triggers in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Building a 3D model of demolition robot in SolidWorks. Li et al [23] improves the layout of the structure and structural rigidity of the robot to ameliorate its dynamic characteristics according to the simulation results of modal analysis. Combining Experimental Modal Analysis (EMA) and Operational Modal Analysis (OMA), the robot frequency response functions as a function arm configuration are determined [24] .…”
Section: Introductionmentioning
confidence: 99%